Studying Concepts of the Breakthrough Economic Reforms in Selected Developed and Developing Countries and Regions of the World: Economic and Legal Aspects - FROLOVA, Еvgenia Еvgenevna; ZANKOVSKY, Sergey Sergeevich; DUDIN, Mihail Nikolaevich; ZINKOVSKY, Sergey Borisovich; KIRSANOV, Aleksey Nickolaevich (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).08, 2018)
The purpose of the present article is to analyze the experience of advanced development of two Asian countries (Japan and China) based on the use of economic breakthrough concepts. The object of study in this article concerns developed and developing countries, as well as transition countries, while research subject involves concepts and models of breakthrough economic reforms in Japan and China. Through the use of several analytical methods (comparative legal and institutional analysis, economic and statistical analysis, and content analysis) we have come up to the following conclusions: economic breakthrough of contemporary developed countries is obviously linked with the technologization as well as modernization of the national production, and economic diversification; developed countries (European Union, North America, and Asia) have established special institutional frameworks (national innovation systems), which allowed creating a competitive product demanded on both the internal and external market, and increasing labor productivity through improving the quality of the workforce (social investment);there are definitely certain similarities in the economic progress of China and Japan (essential involvement of the state in economic processes), however, at the same time these countries are differed by their institutional platforms (in particular, China is open to investment, while Japan focuses on the domestic financial market and the labor market).Results: considering the applicability of economic breakthrough models of Japan and China in relation to Russia, we should note that such models cannot be simply copied to the Russian market without changes (for example, due to the underdeveloped national financial market and insufficient investment attractiveness). Therefore, we suggest in future studies to develop a number of system solutions, which can be used to diversify the Russian raw materials export-based economic model.